Unilateral Absence of the Pulmonary Artery Incidentally Found in Adulthood - Cenk Aypak; Hülya Yıkılkan; Zekai Uysal; Süleyman Görpelioğlu (Case Reports in Medicine)
Unilateral absence of the pulmonary artery (UAPA) or pulmonary artery agenesis is a rare congenital disorder presenting with a wide spectrum of symptoms. UAPA is usually associated with cardiac anomalies and surgically treated in childhood. We report a rare case of a 50-year-old woman who was diagnosed with left pulmonary artery agenesis without any other cardiac anomalies. Clinicians should be aware of the possibility of undiagnosed cases of UAPA in patients through a chest radiograph that suggests the diagnosis. Confirmation of the diagnosis and anatomic details can be discerned by CT scanning.